Peningkatan SDM Menuju Kemandirian UMKM Melalui Kualitas Pendidikan dalam Mewujudkan Sustainable Development Goals - Sonita, Era; Helmi, Helmi (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
Poverty is a major factor in the slow progress of national development. Poverty is caused by the low productivity of a society. Low productivity is caused by the low quality of human resources owned by a country. The low quality of human resources, one of the reasons is the level of education of the community. Education is an important aspect in producing quality human resources. Poor quality of education is a contributing factor to poverty. The need for a concept of quality education